EDUKASI PEMILIHAN JAJANAN SEHAT ANAK USIA SEKOLAH DALAM PENCEGAHAN DIABETES MELITUS DI UPT SDN 060881 - Athira Demitri; Izmi Arisa Putri Lubis; Asnita Yani; Elpriska Elpriska; Balqis Nurmauli Damanik (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2024)
School-aged children tend to prefer foods high in sugar, whether when choosing snacks at school or while shopping with their families. Attractive packaging and bright colors often draw children in, making them perceive such foods as tasty. However, excessive and long-term consumption of sugary foods can increase the risk of diabetes mellitus, a condition that is becoming more prevalent among children. Therefore, to mitigate this risk, it is important to provide education on selecting healthy snacks for school-aged children. This education aims to change children's behavior in choosing healthier snacks, which not only affects their health but also ensures they meet their nutritional needs optimally. This educational activity was held on October 11, 2024, at UPT SDN 060881, targeting 50 students. The program began with an explanation of how to choose healthy snacks and the impact of diabetes mellitus on children. The education session lasted for 60 minutes, followed by a question-and-answer session where five students actively asked questions and shared their experiences in choosing snacks in their daily lives.